Mass Spectrometry A Textbook - Gross, Jürgen H. (Springer Berlin Heidelberg : Imprint: Springer, 2011)
This highly successful textbook, acclaimed for its comprehensiveness,  accuracy, and its many excellent illustrations and photographs now comes in its second edition. Completely revised and substantially extended it  offers: - New chapter on Tandem Mass Spectrometry covering instrumentation, methods for ion activation (CID, ECD, ETD, IRMPD), and applications - New chapter on Ambient Mass Spectrometry (DART, DESI, and more) - New chapter on Inorganic Mass Spectrometry including element speciation and imaging - Learning Objectives for all chapters - Advanced Instrumentation such as orbitraps, linear ion traps, tandem TOFs, FT-ICR and the highly variable hybrid instruments - Updated Problems and Solutions website (www.ms-textbook.com)  Jürgen H. Gross provides in-depth explanations of concepts, methods, and techniques. Students and professionals alike are guided step-by-step from the basics to the successful application of mass spectrometry. Starting from the very principles of gas-phase ion chemistry, isotopic composition, and accurate mass, Jürgen H. Gross leads through the design of all types of mass analyzers and ionization methods to mass spectral interpretation and coupling techniques. His book offers a balanced mixture of practice-oriented information and theoretical background supported by a wealth of references. From reviews of the previous edition: "...one of the best textbooks on mass spectrometry I have seen so far." International Journal of Mass Spectrometry "...can be recommended unreservedly as a textbook and reference source..." Angewandte Chemie, International Edition.